Comparative field performance of oilborne pentachlorophenol versus the substituted isothiazolone DCOI as wood preservatives. (2nd October 2018) - Nicholas, Darrel D.
ABSTRACT: Oilborne pentachlorophenol (penta) is one of the three major wood preservatives employed for treating industrial forest products in the United States (U.S.). However, due to toxicity concerns penta has been listed as a restricted use pesticide in the U.S. for three decades and is no longer permitted in many other countries. A relatively benign substituted isothiazolone, 4, 5 dichloro-N-octylisothiazolin-3-one (DCOI), has good wood preservative properties. This study examined the long-term ground contact performance of samples treated with DCOI versus penta, both formulated using the same oilborne carrier so that the efficacies of the two biocides can be directly compared, at two field test sites with high or severe deterioration in Mississippi. After 25 years of ground contact exposure the decay and termite deterioration ratings indicated that DCOI had equal or slightly more efficacy at about half the retention as samples treated to a penta retention specified for many commercial products.